2021
DOI: 10.1007/s00374-021-01606-9
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-microbial competition for N and plant NO3− uptake rather than BNI determines soil net nitrification under intensively managed Brachiaria humidicola

Abstract: Brachiaria humidicola (syn. Urochloa humidicola) has been acknowledged to control soil nitrification through release of nitrification inhibitors (NI), a phenomenon conceptualized as biological nitrification inhibition (BNI). Liming and N fertilization as features of agricultural intensification may suppress BNI performance, due to a decrease in NI exudation, increased NH3 availability and promotion of ammonia oxidizing bacteria (AOB) over archaea (AOA). A 2-year three-factorial pot trial was conducted to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…So, one hypothesis is that the inconsistency in the results from intensively managed systems could be attributable to variation in soil N fertility status, with high soil N fertility possibly downregulating the expression of the BNI trait, and thus, the N 2 O reduction potential. A recent study indeed suggested that while BNI seems to determine net nitrification rates in extensive pasture systems with B. humidicola, inter-and intra-competition for N between microbes and plants appeared to be the main determinant in intensive systems (Egenolf et al 2022). However, the impact of soil N fertility status on BNI-trait expression is yet to be systematically investigated; more studies into this effect are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, one hypothesis is that the inconsistency in the results from intensively managed systems could be attributable to variation in soil N fertility status, with high soil N fertility possibly downregulating the expression of the BNI trait, and thus, the N 2 O reduction potential. A recent study indeed suggested that while BNI seems to determine net nitrification rates in extensive pasture systems with B. humidicola, inter-and intra-competition for N between microbes and plants appeared to be the main determinant in intensive systems (Egenolf et al 2022). However, the impact of soil N fertility status on BNI-trait expression is yet to be systematically investigated; more studies into this effect are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that AOA can perform nitrification and produce N 2 O under anaerobic conditions. However, the implications of this finding for managed livestock systems requires further investigation, as increased N availability in these systems is likely to favor AOB over AOA (Egenolf et al 2022). In addition, the relative contribution of AOA vs AOB to nitrification in different ecosystems is not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…With this, the involvement of yet undiscovered active ingredients or alternative modes of action could be suggested. Consequently, complementary theories on soil nitrification control are broadly discussed, including microbial N immobilization resulting in the out-competition of ammonia oxidizers, as well as efficient uptake of NO 3 − by plants ( Vázquez et al, 2020 ; Teutscherová et al, 2021 ; Egenolf et al, 2022 ). Here, however, it was our main ambition to verify the existence of so far undiscovered NI.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to fact that AOB was the predominant population of soil nitri ers. 2021), who found that linoleic acid and linolenic acid (BNIs identi ed from Brachiaria humidicola) applied at a concentration of more than 500 mg kg − 1 signi cantly decreased soil net nitri cation rates, most likely as a result of microbial NH 4 + -N and/or NO 3 − -N immobilization Egenolf et al (2022). noted that…”
mentioning
confidence: 99%